A Case Report on Etoricoxib Induced Stevens Johnson Syndrome - Kumar, Poludasari Shravan; Tharuni, Bomma (Journal of Pharmacy Practice and Community Medicine)
Etoricoxib is a selective cyclo-oxygenase enzyme-2 (COX-2) inhibitor which is majorly indicated in the treatment of inflammatory disorders such as rheumatoid arthritis, osteoarthritis and gout. Etoricoxib selectively inhibits COX-2 thereby inhibiting the conversion of arachidonic acid to prostaglandins (PG’s). Stevens–Johnson Syndrome (SJS) is a rare, life threatening hypersensitivity reaction that predominantly affects skin and mucous membrane which is characterised by extensive epidermal necrosis. Some of the medications which are associated with the development of Stevens Johnson syndrome include xanthine oxidase inhibitors such as allopurinol, antiepileptic medications such as carbamazepine, lamotrigine, phenytoin and Non-Steroidal Anti-Inflammatory Drugs (NSAID’s). In this case report, we summarize regarding a patient who developed SJS after usage of etoricoxib that was managed by cessation of the offending agent and symptomatic treatment concomitant with supportive care.
Keywords: Cyclo-Oxygenase enzyme-2 (COX-2); Prostaglandins (PGs); Hypersensitivity; Necrosis; Non- Steroidal Anti-Inflammatory Drugs (NSAID’s).